Characterization of bacteria type strain Bacillus. spp isolated from extracellular polymeric substance harvested in seafood wastewater. Issue 2 (7th September 2021) - Tran, Thi Ngoc Thu; Nguyen, Thi Dong Phuong; Dinh, Ha Thuong; Bui, Thi Tho; Ho, Le Han; Nguyen‐Phan, Truc Xuyen; Khoo, Kuan Shiong; Chew, Kit Wayne; Show, Pau Loke
Abstract: Bacillus species have been well‐documented as bacteria isolated from soil with primary characteristics that were identified and applied to agriculture, wastewater treatment, pharmaceutic, and human life. This study focuses on the characterization of Bacillus strains isolated from a particular resource, which is seafood wastewater, and to list which correlating and different properties with those coming from soil. Of the 15 isolates obtained by positive Gram (+) screening, 14 sequenced Bacillus genomes type strain B. subtilis ( B. subtilis ) and Bacillus cereus ( B. cereus ), which were analyzed by the phylogenetic tree, were chosen for further investigation due to their majority. For antagonistic activity against E.coli ATCC 85922, no visible inhibitory zones were directly observed to isolates type strain B. cereus . On the other hand, out of the four B. subtilis exploited in this activity with AU > 200, only one exhibited a strong AU of 327. In the case of antibiotic susceptibility, B. subtilis was sensitive to most of the five antibiotics investigated in this study, particularly to the high coefficient of cell's susceptibility over 0.8 against penicillin and tetracyclin. Additionally, the critical property in biofilm production (elucidated isolates) was amplified with two genes abrB and spo0A, and was exhibited through SEM visualization. © 2021 Society of Chemical Industry (SCI).